Detection of Natural White Spot Caries Lesions by an Ultrasonic System - (:unkn) unknown (S. Karger AG, 2000)
Ultrasound has been used in industrial business as one of the nondestructive measurement methods. It was hypothesized that nondestructiveness of the ultrasonics could be useful in determination of demineralization of noncavitated carious lesions on human enamel. This investigation was designed to determine the presence of natural carious lesions on proximal surfaces of human molar teeth using an ultrasonic system compared to radiography and histology as the gold standards. Measurements were made directly from proximal surfaces of 20 mandible molar teeth with white spot carious lesion by 2 examiners independently with the ultrasonic system. Ultrasonic evaluation of each natural white spot lesion had a sensitivity of 88%, specificity of 86%, positive predictive value of 88% and a negative predictive value of 86%, and the chance-corrected agreement was also satisfactory (N = 0.74) compared to histology. The radiograph demonstrated chance-corrected agreement of 0.41:0.38 for the first and second examiners, respectively. Duncan test analysis of the numerical values was significantly different for the intact and the noncavitated carious surfaces (p < 0.05). The results indicated that the ultrasonic evaluation is a sensitive method for the detection of the natural white spot carious lesions and can differentiate the changes in elastic properties of enamel numerically. Copyright ©2000 S. Karger AG, Basel.
Keywords: Diagnosis; Natural carious lesion; Ultrasonic